On Several Issues of the Current Theoretical Discourse on Censorship - Pavel Matejovič (Slovenska Literatura, 2017)
The author of the paper deals with an overview of reflection on censorship in the current literary theoretical discourse focusing on the Czech cultural context. He pays special attention to the two-volume monograph titled v Obecném záujmu / In Public Interest/ and the anthology of theoretical studies which were pubished under the title Nebezpečná literatura? /Dangerous Literature?/. He draws attention to the theoretical works by P. Bourdieu, J Butler and L. Losev. He puts individual theoretical findings into relation with contemporary poetics as it was formed by the canon of Socialist Realism (cryptic forms of Esopian language in the contemporary satire). He also pays attention to dispersed forms of censorship which formed the poetics of the 1970s and the 1980s during the period of so-called Normalization (the formation of parallel circulation).